ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA TERHADAP PERS YANG MELAKUKAN TINDAK PIDANA PENGHINAAN DAN PENCEMARAN NAMA BAIK BERDASARKAN PASAL 310 AYAT 3 KUHP - Tiara Vemilya; Erdianto Erdianto; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Persed of social community which functions as a control, order, and educational media whose existence is guaranteed based on the constitution. The legal threat most often referred to by the press or mass media is articles of defamation or defamation. A person can easily accuse the press of insulting or defaming him if he does not like the way the press presents himself. This has led to articles on defamation that are often called mines to the press, as they are easily imposed to sue the press or journalists. Take the example of the Mara Salem Harahap case which made news on Lassernewstoday.com about alleged corruption involving the Regent of Simalungun. Then the defendant was sentenced to prison for 1 year. This distorts press freedom. These objectives: First, to see how the press is accountable for committing criminal acts of insult and defamation based on Article 310 Paragraph 3 of the Criminal Code. Second, the application of Article 310 Paragraph 3 of the Criminal Code is aimed at the press or all circles.This type of research used normative juridical research. This research uses legal synchronization, synchronization aims to reveal the reality to what extent a particular statute is harmonious vertically or horizontally, if the legislation is equal and belongs to the same field.From the results of the research, it can be denied that: First, the right of reply is not used on the party who is aggrieved so that it is subject to Article 27 paragraph 3 of the Electronic Transaction Information Law. Article 27 Paragraph 3 relates to Article 310 of the Criminal Code. Then an excuse can be given to the press who commits criminal acts of insult and defamation for the sake of the public interest and call himself. Second, of course, article 310 paragraph 3 of the Criminal Code concerns the reason for the right to eradicate crime for everyone. Author's suggestion, First to the government to make policies regarding restrictions on expression. Second, the excuse of a criminal offence should not be misused.Keywords: Press - Insult - Defamation - Criminal Abolition